New approaches to Avar social identities in the Balaton region of the Carpathian Basin - AD. 550 to 900: evidence from Keszthely-Fenékpuszta - Gal, G. A. (2023)
‘Avar’ identities and affiliations were constructed in the Carpathian Basin from a combination of new influences from the western Eurasia Steppe (brought by people through population movements and exchange/trade) and by the existing descendants of the Roman provincial population. They were also influenced by earlier settlers from the Steppes in the era of the Hunnic Confederacy in the later fourth and fifth centuries and by influences and people originally from the Baltic region (Lombards and Gepids) by the sixth century. Although the Avars strongly shaped the other European communities' economic, cultural, and political organisation, their ruling and lifestyle habits are little understood.